Jeff Manza and Clem Brooks, Social Cleavages and Political Change. Voter Alignments and U.S. Part Coalitions, Oxford: Oxford University Press, 1999, 342 + xi s.. £35.00. - Sommer Harrits, Gitte (Politica, 2001)
-